Study of the Groundwater Flow During Excavation Work at Construction Site - Kasim, Narimah; Zailani, Nor Syahirah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
The construction industry often experiences a variety of problems, especially regarding groundwater flow during excavation work at construction sites. Construction structures built on sites with rising groundwater surface have many challenges in the field of geotechnics. The increase in water surface in Malaysia is due to the infiltration of heavy rainfall and precipitation into the soil. The high-water tables induce negative effects on the construction buildings. This study focuses on adding more knowledge about extreme groundwater levels to avoid structural damage or building environment due to very high groundwater flow. Typically, the spread of extreme groundwater levels is due to interpolation between results obtained from the analysis of local extreme values in groundwater observation wells. Among other factors that affect groundwater during excavation work, is because the flow of water is not controlled according to appropriate methods. In addition, during construction activities, uncontrolled groundwater flow can cause damage to building infrastructure, even the maintenance cost for this problem is very high. Therefore, the purpose of this research is to improve the management techniques that form and solve the problem of rising groundwater flow at the construction site during excavation works. The objective of this research was to study the current practices, to identify the challenges, and to determine the improvement ways to controlling groundwater flow during excavation work at construction sites. This research uses a qualitative method through semi -structured interview questions for the data collection process. The respondents of this research are among the contractors registered with the Construction Industry Development Board (CIDB) Grade G7 in Johor and Selangor because these two states have the same type of soil, namely clay soil. Furthermore, the respondents are very important for this qualitative approach to ensure that all data obtained from the respondent is accurate and to answer the question on the basis of the respondent’s work experience. Based on the respondents’ experience, this study is very helpful for researchers to get more information about groundwater flow that often occurs at construction sites.